Sliding wear of SiC reinforced duplex stainless steel via TIG torch surface melting technique - Maleque, Md. Abdul; Azwan, Muhammad; Afiq, Muhammad M. (Bentham Science Publishers, 2020)
This paper aimed to investigate the wear properties of surface modified duplex stainless steel (DSS) with SiC particle preplacement using tungsten inert gas (TIG) torch surface melting technique under different process parameters. Surface modification of DSS via TIG torch technique in previous patents is scared. Surface layer was produced using silicon carbide (SiC) particles on DSS substrate in order to form a new hard surface with intermetallic compound material. The effect of particle size, SiC preplacement, heat input and shielding gas flow rate on surface topography, hardness and wear rate were investigated. Observation of surface topography showed rippling marks which confirms that re-solidification process has been taken place during TIG melting. The analyzed result showed that preplacement of SiC particles via TIG torch melting technique increased the hardness of DSS by ~ five times. As the hardness increases, wear resistance of the surface layered DSS also increased accordingly.